Song search tool - Sun, Albrert Keh Seng (Universiti Malaysia Sarawak, UNIMAS, 2005)
With the significant change of technology, various type of application are put into the market every day. These applications are tailored for some specific purposes. Searching tool is developed for searching files whereas media player is for playing songs. There is no application that can perform both the search and playback function.